Effects of malted and non-malted whole-grain wheat on metabolic and inflammatory biomarkers in overweight/obese adults: A randomised crossover pilot study. (1st March 2016) - Nelson, Kristina; Mathai, Michael L.; Ashton, John F.; Donkor, Osaana N.; Vasiljevic, Todor; Mamilla, Ravikumar; Stojanovska, Lily
Highlights: Malted-wheat may supply additional dietary antioxidants compared with non-malted wheat. Malted-grain food products offer potential as a functional food. Extended trials testing malted-wheat in vivo are warranted. Abstract: Metabolic dysfunction in obesity may be attenuated by whole-grain intake, which has been attributed to synergistic actions of bioactive compounds. Germination/malting may increase grain bioactives, including polyphenols, however biological effects compared with non-germinated grains are unclear. Polyphenols and biological effects were compared between malted-wheat (MLT) and whole-grain wheat (CON) breakfast cereals. Polyphenol content and antioxidant activity were significantly higher ( P < 0.01 and P < 0.05, respectively) in MLT. Corresponding obesity-related biomarkers were measured in 10 overweight/obese adults in a 2 × 4-week double-blind, randomised, crossover trial. Following both interventions, diastolic blood pressure reduced significantly with time ( P < 0.05) and low-density lipoprotein increased slightly ( P < 0.05) over time. A significant time * cereal effect ( P < 0.05) was found for insulin resistance, decreasing following CON and increasing with MLT. No other significant metabolic or inflammatory differences were found. Whilst MLT contained significantly increased polyphenols, cumulative effects in attenuating obesity-related metabolic dysfunction may require increased consumption.